O jednych zajęciach z kultury żywego słowa - Ogłoza, Ewa (Z Teorii i Praktyki Dydaktycznej Języka Polskiego, 2007)
The article constitutes a description of selected classes in the culture of the living word, an important subject taught in the course of the Polish philology studies for those who chose teaching specialization. On the basis of Powiedz, że wkrótce, a lyric by Stanislaw Barańczak (from the volume of Chirurgiczna precyzja), I was trying to show how meaningful this poem is, and how many contexts one should rest on to broaden its interpretation, combining the issues of a literary, linguistic, existential and executive nature.